5(P-8)=P+3

Simple and best practice solution for 5(P-8)=P+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(P-8)=P+3 equation:


Simplifying
5(P + -8) = P + 3

Reorder the terms:
5(-8 + P) = P + 3
(-8 * 5 + P * 5) = P + 3
(-40 + 5P) = P + 3

Reorder the terms:
-40 + 5P = 3 + P

Solving
-40 + 5P = 3 + P

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Add '-1P' to each side of the equation.
-40 + 5P + -1P = 3 + P + -1P

Combine like terms: 5P + -1P = 4P
-40 + 4P = 3 + P + -1P

Combine like terms: P + -1P = 0
-40 + 4P = 3 + 0
-40 + 4P = 3

Add '40' to each side of the equation.
-40 + 40 + 4P = 3 + 40

Combine like terms: -40 + 40 = 0
0 + 4P = 3 + 40
4P = 3 + 40

Combine like terms: 3 + 40 = 43
4P = 43

Divide each side by '4'.
P = 10.75

Simplifying
P = 10.75

See similar equations:

| -8(x+6)=6v-34 | | (-5/6)(x-7) | | w-69=-63 | | 4x+80=50x-12 | | 7=32+b | | -19-6k=6(1+3k) | | 2,3f+12=40 | | 6x^9/x^2 | | 17x-3=9x+13 | | 49x^2-56+16= | | 3t^2-24t+45=0 | | 4p+12= | | (N+4)*3=36 | | 6x+2=3x+7 | | A/6-1=7 | | 11=r/13 | | x/5=4/16 | | 2x+6=3x-9 | | 3x+5=55-9x | | 3x-6.8=31 | | 7d-12=38 | | 125-6x=30x+21 | | 8x^2=5x+7 | | 3/4=9/x-7 | | -2-z=4.5 | | (6-x)/(x-2)-(5x-7)/(2-x) | | 6=-8x-2 | | 114-10x=9x+19 | | 752.6-78.85= | | x+1/6=x-1/x | | 6x-5=7x+5 | | 2-5r=4-2r |

Equations solver categories